OP01 Chronic physical illness in early life and risk of chronic regional and widespread pain at age 68: Evidence from the MRC National Survey of Health and Development. (13th September 2016) - Muthuri, SG; Kuh, D; Bendayan, R; Macfarlane, G; Cooper, R
Abstract : Background: A growing number of people who experienced chronic illness in early life are surviving into later adulthood. These people are especially vulnerable to a disproportionate burden of morbidity and disability during adulthood. However, previous studies testing the hypothesis that serious illness in early life increases the risk of chronic pain in adulthood are few and show inconsistent findings. We aimed to examine the associations between chronic physical illnesses in earlier life and risk of chronic widespread and regional pain in old age. Methods: Hypotheses were tested using data from the MRC National Survey of Health and Development (NSHD). Serious illness in early life was defined as any experience of physical illness before age 25 years that required hospital admission of at least 28 days. Pain was self-reported at age 68, and chronic widespread pain (CWP) was defined according to American College of Rheumatology criteria. Multinomial logistic regression was used to investigate associations of serious illness in early life with three categories of pain: CWP, chronic regional pain (CRP) and other pain, with no pain as the referent category. Adjustment was made for sex and: socioeconomic position (education attainment, occupational class); adult health status (BMI, longstanding illness or health problems); health behaviours (smoking, physical activity); and psychosocial factors (parental divorce and symptoms of anxiety and depression). All analyses were performed using STATA v12.1. Results: Of 2401 NSHD participants with complete data on both serious illness in early life and pain at age 68, a total of 1339 (55.6%) reported pain, with the highest proportion reporting CRP (30.2%). 11% reported CWP (13.2% of women and 7.7% of men, p for sex difference < 0.001). Compared with those with no history of serious illness, those who had at least one serious illness in early life had a higher likelihood of CWP (Relative-Risk Ratio (RRR) = 1.62 [95% CI: 1.21–2.17]) and of CRP (RRR = 1.25 [95% CI: 1.01–1.54]) after adjusting for sex. In fully adjusted models, serious illness in early life was associated with CWP (RRR = 1.43 [95% CI: 1.05–1.95]) but associations with CRP had attenuated (RRR = 1.19 [95% CI: 0.96–1.48]). There was no association with other pain in any model. Conclusion: Associations between serious illness in early life and chronic pain may persist into old age; therefore interventions that prevent or alleviate burdens arising from serious illness may need to start early. Future studies that examine the association between serious illness and incidence and/or longitudinal course of chronic pain in older adults are needed.